Implementasi Strategi Digital Marketing Dalam Meningkatkan Penjualan Pada Usaha Fashion Muslim Toko Barokatuna Tambakberas, Jombang - Islachiyana, Rifda; Amarudin, Amin Awal; Amala, Karisma Wahyu; Agil, Muhammad (Jurnal Kajian Ekonomi dan Manajemen Indonesia (JKEMI), 2023)
The development of internet technology has marked the beginning of the industrial revolution era 5.0. In product marketing, the use of information technology allows consumers to know the product with a wider range. The ability to access information quickly and easily is a new opportunity for MSMEs. This study aims to understand marketing strategies that have been implemented appropriately through digital marketing and introduce Muslim fashion products widely. This research method is qualitative using a case study approach. Research results show that barokatuna stores tend to prefer to market products online because it can increase the number of sales. The most common strategy used in implementing digital marketing to market products is through social media such as reseller groups, e-commerce platforms such as shopee, and also through WhatsApp status.